Government policy and the distribution of income in Peru, 1963-1973 - Webb, Richard Charles (Cambridge, Mass. : Harvard University Press, 1977)
This book attempts to measure the impact of government policy on the distribution of income in Peru since 1963
Includes bibliographical references and index.
osa 21/09/2018
Loans
Keywords: Income distribution; Income; Peru